Peningkatan Kapasitas Masyarakat Cimanggu Melalui Ecobrick dan Sabun Ramah Lingkungan sebagai Solusi - Marlina, Lusi; Damayanti, Eva; Yuliana, Ade; Paryati, Retno (ASOSIASI IDEBAHASA KEPRI, 2025)
This community service activity aims to realize the work program of the chemical engineering study program, serve the community, build a spirit of mutual cooperation and social care, and prepare students in accordance with the development and demands of society. The target of the activity is the community of Cimanggu Village, Ngamprah District, West Bandung Regency. This activity is based on Pancasila, Tri Dharma Perguruan Tinggi, and chemical engineering study program. The activity took place over two days, June 24-25, 2023, in Cimanggu Village. The first day was filled with persuasion to the community, and the second day was filled with socialization about making ecoenzymes from vegetable and fruit waste as soil fertilizers, and making tofu nuggets with the residents. This activity has been carried out well, and the entire series of events have been realized, including persuasion of residents, making ecoenzymes, socializing tofu nuggets, and helping residents with gardening. The response of the residents was quite enthusiastic.